Platycephalus orbitalis, a new species of flathead (Teleostei: Platycephalidae) collected from western Australia - Imamura, Hisashi; Knapp, Leslie W. (Zootaxa, 2009)
A new plataycephalid, Platycephalus orbitalis, is described on the basis of specimens collected in the Indian Ocean off the coast of Western Australia at depths of 50–144 m. The new species had been mistakenly identified as P. marmoratus, which is now known to be restricted to eastern Australia. Several morphological characters (e.g, 65–68 pored scales in lateral line, snout and interorbit naked, and caudal fin blackish with white posterior margin) can separate Platycephalus orbitalis sp. nov. and P. marmoratus from the other 14 congeners. In addition, Platycephalus orbitalis sp. nov. differs from P. marmoratus in having the margin of the interopercle scalloped, skinny sensory tubes on the infraorbitals, the preopercle well developed and mostly covering the cheek region, and the body and head lacking distinct large spots and bands dorsally.